Rat pancreatic stellate cells secrete matrix metalloproteinases: implications for extracellular matrix turnover. (1st February 2003) - Phillips, P A; McCarroll, J A; Park, S; Wu, M-J; Pirola, R; Korsten, M; Wilson, J S; Apte, M V
Abstract : Background: Pancreatic fibrosis is a characteristic feature of chronic pancreatic injury and is thought to result from a change in the balance between synthesis and degradation of extracellular matrix (ECM) proteins. Recent studies suggest that activated pancreatic stellate cells (PSCs) play a central role in pancreatic fibrogenesis via increased synthesis of ECM proteins. However, the role of these cells in ECM protein degradation has not been fully elucidated. Aims: To determine: (i) whether PSCs secrete matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinases (TIMPs) and, if so (ii) whether MMP and TIMP secretion by PSCs is altered in response to known PSC activating factors such as tumour necrosis factor α (TNF-α), transforming growth factor β1 (TGF-β1), interleukin 6 (IL-6), ethanol, and acetaldehyde. Methods: Cultured rat PSCs (n=3–5 separate cell preparations) were incubated at 37°C for 24 hours with serum free culture medium containing TNF-α (5–25 U/ml), TGF-β1 (0.5–1 ng/ml), IL-6 (0.001–10 ng/ml), ethanol (10–50 mM), or acetaldehyde (150–200 μM), or no additions (controls). Medium from control cells was examined for the presence of MMPs by zymography using a 10% polyacrylamide-0.1% gelatin gel. Reverse transcriptase-polymerase chain reaction (RT-PCR) was used to examine gene expression of MMP9 and the tissue inhibitors of metalloproteinases TIMP1 and TIMP2. Western blotting was used to identify a specific MMP, MMP2 (a gelatinase that digests basement membrane collagen and the dominant MMP observed on zymography) and a specific TIMP, TIMP2. Reverse zymography was used to examine functional TIMPs in PSC secretions. The effect of TNF-α, TGF-β1, and IL-6 on MMP2 secretion was assessed by densitometry of western blots. The effect of ethanol and acetaldehyde on MMP2 and TIMP2 secretion was also assessed by this method. Results: Zymography revealed that PSCs secrete a number of MMPs including proteinases with molecular weights consistent with MMP2, MMP9, and MMP13. RT-PCR demonstrated the presence of mRNA for metalloproteinase inhibitors TIMP1 and TIMP2 in PSCs while reverse zymography revealed the presence of functional TIMP2 in PSC secretions. MMP2 secretion by PSCs was significantly increased by TGF-β1 and IL-6, but was not affected by TNF-α. Ethanol and acetaldehyde induced secretion of both MMP2 and TIMP2 by PSCs. Conclusions: Pancreatic stellate cells have the capacity to synthesise a number of matrix metalloproteinases, including MMP2, MMP9, and MMP13 and their inhibitors TIMP1 and TIMP2. MMP2 secretion by PSCs is significantly increased on exposure to the proinflammatory cytokines TGF-β1 and IL-6. Both ethanol and its metabolite acetaldehyde increase MMP2 as well as TIMP2 secretion by PSCs. Implication: The role of pancreatic stellate cells in extracellular matrix formation and fibrogenesis may be related to their capacity to regulate the degradation as well as the synthesis of extracellular matrix proteins.